2018
DOI: 10.14260/jemds/2018/572
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Incidental Lumbar Spondylolysis by Computed Tomography

Abstract: BACKGROUND Spondylolysis is defined as a defect in the pars interarticularis of the vertebral arch, which is a bony bridge connecting the superior and the inferior articular facet joints. Aims and Objectives: To determine the incidental occurrence of lumbar spondylolysis, the common site and type of involvement and the associated degenerative disorders in the patients in an unselected population. MATERIALS AND METHODS This is a cross-sectional study in which incidental spondylolysis was evaluated for 852 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…However, another study conducted in India showed a prevalence of 12.5% spondylolysis on examining 852 consecutive patients with abdomen CT in an unselected Indian population which was significantly higher than our study. 12 The possible explanation for the slightly higher rate identified in the current study is the use of CT scan. This imaging modality is currently considered the gold standard in terms of identifying spondylolysis, particularly in the setting of unilateral defects, and non-displaced bilateral defects.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, another study conducted in India showed a prevalence of 12.5% spondylolysis on examining 852 consecutive patients with abdomen CT in an unselected Indian population which was significantly higher than our study. 12 The possible explanation for the slightly higher rate identified in the current study is the use of CT scan. This imaging modality is currently considered the gold standard in terms of identifying spondylolysis, particularly in the setting of unilateral defects, and non-displaced bilateral defects.…”
Section: Discussionmentioning
confidence: 61%
“…However, another study conducted in India showed a prevalence of 12.5% spondylolysis on examining 852 consecutive patients with abdomen CT in an unselected Indian population which was significantly higher than our study. 12 …”
Section: Discussionmentioning
confidence: 99%
“…However, it is generally accepted that the etiology of spondylolysis is multifactorial, involving a congenital weakness of the pars interarticularis that results in a fracture caused by repeated stress (Figure 1). Spondylolysis is commonly reported in both clinical (e.g., Chellathurai et al, 2018;Leone et al, 2011;Mansfield & Wroten, 2021) and bioarchaeological literature (e.g., D'Angelo del Campo et al, 2017;Plomp et al, 2012;Ponce, 2010), with a past prevalence of between 3% and 54% (Merbs, 1983;Simper, 1986) and between 3% and 12.5% in living populations (Chellatharai et al, 2018;Eisenstein, 1978). However, prevalence can be higher in athletes, such as gymnasts and wrestlers, in some cases reaching up to 60% (Iwamoto et al, 2004;Sairyo et al, 2011;Tezuka et al, 2017).…”
Section: Introductionmentioning
confidence: 99%